Synthesis of 1-Substituted-3-(2’-hydroxy-3’-chloro-5’-ethyl phen-1’-yl)-5-aryl-2-pyrazoline - Vashi, Kamal; Naik, H.B. (Asian Journal of Chemistry, 2016)
2'-Hydroxy-3'-chloro-5'-ethyl acetophenone chalcones (1) reacted with hydrazine hydrate in ethanol to give 1-H-3-(2'-hydroxy-3'-chloro-5'-ethyl phen-1'-yl)-5-aryl-2-pyrazolines (2), 1-benzoyl pyrazolines (3) and 1-nitroso pyrazolines (4) were prepared from pyrazolines (2) by reacting with benzoyl chloride in pyridine and sodium nitrate in HCl respectively. Structural elucidations were done on the basis of elemental and spectral analysis. The antibacterial activity has also been screened.